ANALISIS PERBANDINGAN PENERIMAAN BADAN LAYANAN UMUM DI SEKTOR JASA INDUSTRI - Kalam, Rizalul; Miftahudin, Erwin; Surtikanti, Surtikanti (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
Public service agencies in the industrial services sector, also known as BLUs, play a crucial role in supporting national industrial growth. However, there are discrepancies in the level of non-tax state revenue (PNBP) among BLUs, which require further analysis. This study aims to compare the PNBP of four BLUs, selected based on their organizational age groups, using nonparametric statistical methods. Specifically, Welch’s ANOVA and the Kruskal-Wallis test were employed to examine revenue differences among the entities, followed by Dunn’s Post Hoc-Test to identify entity pairs with significant differences. The results of Welch’s ANOVA and the Kruskal-Wallis test indicated significant variations in revenue among the entities. Dunn’s Post-Hoc Test revealed that older entities had significantly higher revenue compared to newly established entities. However, no significant differences were observed among entities established in the same year. This finding suggests that older entities tend to have higher revenue, which can be attributed to the organizational life cycle theory, economies of scale, and industrial reputation. Institutions with longer operational histories are likely to have greater operational stability and industry trust, leading to higher revenue.